Will Artificial Intelligence Reshape the Global Workforce by 2030? A Cross-Sectoral Analysis of Job Displacement and Transformation - Sugandha Chhibber; S.R. Rajkumar; Sandun Dassanayake (WISE Pendidikan Indonesia, 2025)
The rapid advancement of artificial intelligence (AI) is transforming the global labor market, presenting both opportunities and challenges. This study investigates the extent of AI-driven job displacement and task transformation across industries, highlighting sector-specific vulnerabilities and workforce perceptions. Using secondary data from Statista’s global surveys (2022–2023), involving 22,816 employees, 1,684 business leaders, and 803 corporations, the study employs descriptive statistical analysis to identify patterns of job disruption and skill adaptation. The findings reveal that AI primarily reshapes job functions rather than eliminating entire occupations, with 57% of respondents reporting task augmentation and 36% expressing concern about job loss. Routine-based sectors, such as manufacturing and customer service, face higher displacement risks, while knowledge-based professions, including healthcare, education, and creative industries, experience AI as a complementary tool. Additionally, disparities in AI adoption are evident between large corporations and small-to-medium enterprises (SMEs), often due to resource limitations and varying digital readiness. The study concludes that successful AI integration hinges on proactive strategies, including continuous workforce reskilling, adaptive education systems, and ethical AI deployment. Policymakers, industry leaders, and educational institutions must collaborate to ensure an inclusive transition, prioritizing digital literacy and skills development. Future research should explore regional variations, firm-level case studies, and the long-term socio-economic impacts of AI adoption. Ultimately, this study underscores the importance of balancing technological advancement with workforce resilience to foster sustainable economic growth in an AI-driven era.